PENERAPAN STRATEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 019 KAMPUNG DAGANG KECAMATAN RENGAT KABUPATEN INDRAGIRI HULU - Riko Sari; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research was motivated by the facts that occurred in class IV SDN 019 Kampung Dagang show low learning outcomes IPS. The problem of this research is "Does the implementation of inquiry learning strategies to improve learning outcomes social studies in class IV SDN 019 Kampung Dagang Kecamatan Rengat Kabupaten Indragiri Hulu?". The purpose of this research to improve learning outcomes of social studies class IV through the implementation of inquiry learning strategies in in class IV SDN 019 Kampung Dagang Kecamatan Rengat Kabupaten Indragiri Hulu. This study took place in the class SDN 019 Kampung Dagang and executed on 26 March until 30 April 2016, with the number of subjects as many as 25 people consisting of 10 male students and 15 female students. This research is a classroom action research conducted in two cycles. Based on the results obtained by the percentage of individuals and classical completeness by applying inquiry learning strategy, before action is taken only 16% has been completed, after the action on the first cycle increased by 56% completeness and the second cycle increased by 88%. Differences increase learning outcomes in basic score is 68% and increased to 78 in the first cycle, the difference between the increase of the value of the results of the previous study was 14.7%. In the second cycle the average student learning outcomes back increased to 82% margin improvement that occurred from the first cycle to the second cycle was 5.1%, so an increase in the value of student learning outcomes as a whole was 19.8%. Based on the above it can be concluded the implementation of inquiry learning strategy is excellent for improving learning outcomes Social Science in class IV S IV SDN 019 Kampung Dagang Kecamatan Rengat Kabupaten Indragiri Hulu. Keywords: Inquiry Learning Strategy, Learning Outcomes, IPS